1990
DOI: 10.1139/v90-230
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of oxidation of iodide ion by the molybdenum (VI) – hydrogen peroxide system

Abstract: ). The kinetics of oxidation of potassium iodide by hydrogen peroxide in aqueous perchloric acid has been studied both in the The activation energies associated with rate constants kl, k2, and k3 are 52 ? 1, 49 t 1, and 42 ? 3 kJ mol-', respectively.A mechanism in agreement with the experimental kinetic data is proposed, according to which rate constants k, , k2, and k3 correspond to the oxidations of iodide ion by H202. H302+ and H2Mo05, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 12 publications
(31 reference statements)
2
14
0
Order By: Relevance
“…The order of reaction with respect to the oxidant and the reductant was determined by implementing a series of equations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The reaction was probed under the pseudo-first order-condition via keeping reductant in excess over oxidant.…”
Section: Order and Rate Constant Of The Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The order of reaction with respect to the oxidant and the reductant was determined by implementing a series of equations (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The reaction was probed under the pseudo-first order-condition via keeping reductant in excess over oxidant.…”
Section: Order and Rate Constant Of The Reactionmentioning
confidence: 99%
“…The oxidation of the iodide ion and its mechanism under different experimental conditions has been of interest for years due to its applications especially in energy production and solar cells. [1][2][3][4][5][6][7][8][9] A number of studies explored the mechanism of the oxidation of the iodide ion by various transition metal complexes that can be used to enhance the efficiency of the dye-sensitized solar cells (DSSCs). The applications of transition metal complexes based upon ruthenium, cobalt, copper, nickel, and iron metals have been surfaced as sensitizers in DSSCs.…”
Section: Introductionmentioning
confidence: 99%
“…18 Several oxyanions including sodium molybdate 19 will catalyse the oxidation of the iodide ion by hydrogen peroxide. Hydrogen peroxide or sodium perborate with sodium tungstate as the catalyst and potassium iodide as the source of iodine, have both been used 20 for the iodination of aromatic amides.…”
Section: Iodination Using Other Oxidantsmentioning
confidence: 99%
“…The use of hydrogen peroxide as an oxidant for the iodination of activated arenes with either iodine or potassium iodide has been used for many years. 18 Several oxyanions including sodium molybdate 19 will catalyse the oxidation of the iodide ion by hydrogen peroxide. Hydrogen peroxide or sodium perborate with sodium tungstate as the catalyst and potassium iodide as the source of iodine, have both been used 20 for the iodination of aromatic amides.…”
Section: Iodination Using Other Oxidantsmentioning
confidence: 99%
“…Chloroperoxidase and bromoperoxidase 2 enzymes and model systems that mimic their activity , use a transition metal (heme-bound iron for chloroperoxidase, non-heme vanadium for bromoperoxidase) 2c to activate H 2 O 2 for the oxidation of halide to halogen or hypohalous acid. Model studies have shown that chloride, bromide, , and iodide can be oxidized by such catalysis and that the metal undergoes sequential one-electron steps. These biomimetic reactions are important to chemistry in general in that they perform many desired chemical transformations such as epoxidations and halogenations in an environmentally acceptable way.…”
mentioning
confidence: 99%